Accelerometer and Gyroscope Based Gait Analysis Using Spectral Analysis of Patients with Osteoarthritis of the Knee - WIELAND STAAB; RALF HOTTOWITZ; CHRISTIAN SOHNS; JAN MARTIN SOHNS; FABIAN GILBERT; JAN MENKE; ANDREE NIKLAS; JOACHIM LOTZ (Journal of Physical Therapy Science, 2014)
[Abstract.] [Purpose] A wide variety of accelerometer tools are used to estimate human movement, but there are no adequate data relating to gait symmetry parameters in the context of knee osteoarthritis. This study's purpose was to evaluate a 3D-kinematic system using body-mounted sensors (gyroscopes and accelerometers) on the trunk and limbs. This is the first study to use spectral analysis for data post processing. [Subjects] Twelve patients with unilateral knee osteoarthritis (OA) (10 male) and seven age-matched controls (6 male) were studied. [Methods] Measurements with 3-D accelerometers and gyroscopes were compared to video analysis with marker positions tracked by a six-camera optoelectronic system (VICON 460, Oxford Metrics). Data were recorded using the 3D-kinematic system. [Results] The results of both gait analysis systems were significantly correlated. Five parameters were significantly different between the knee OA and control groups. To overcome time spent in expensive post-processing routines, spectral analysis was performed for fast differentiation between normal gait and pathological gait signals using the 3D-kinematic system. [Conclusions] The 3D-kinematic system is objective, inexpensive, accurate and portable, and allows long-term recordings in clinical, sport as well as ergonomic or functional capacity evaluation (FCE) settings. For fast post-processing, spectral analysis of the recorded data is recommended.